2018
DOI: 10.21203/rs.2.41/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study between intrathecal dexmedetomidine and intrathecal magnesium sulfate in prevention of post spinal shivering in uroscopic surgery. (RCT)

Abstract: Background: Hypothermia and shivering are associated common complications after spinal anesthesia especially in uroscopic procedures when large amounts of cold intraluminal irrigating fluids are used. Among all adjuvants that have been used in literatures for shivering management, magnesium sulphate and dexmedetomidine were the most effective with least side effects. Our aim of the study is to compare the effect of intrathecal dexmedetomidine versus intrathecal magnesium sulfate in prevention of post spinal sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Sufentanil has been used as a local anesthetic in spinal blocks for labor analgesia in many previous studies; 4 therefore, intrathecal injection of sufentanil combined with epidural ropivacaine and sufentanil was the positive control in the present study. Dex has also been reported to maintain stability, relieve pain, prevent chills without respiratory depression when used as an intrathecal drug, 20,21 and improve intrathecal and epidural blocks. 22,23 Mohamed et al reported that Dex given intrathecally to patients undergoing major abdominal cancer surgery for postoperative analgesia could improve and prolong analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil has been used as a local anesthetic in spinal blocks for labor analgesia in many previous studies; 4 therefore, intrathecal injection of sufentanil combined with epidural ropivacaine and sufentanil was the positive control in the present study. Dex has also been reported to maintain stability, relieve pain, prevent chills without respiratory depression when used as an intrathecal drug, 20,21 and improve intrathecal and epidural blocks. 22,23 Mohamed et al reported that Dex given intrathecally to patients undergoing major abdominal cancer surgery for postoperative analgesia could improve and prolong analgesia.…”
Section: Discussionmentioning
confidence: 99%